Influence of Lower Substrate pH and Retention Time on the Efficiency of a UASB Bioreactor Treating Winery Waste Water - Ronquest, L.C.; Britz, T.J. (South African Journal of Enology and Viticulture, 2017)
A mesophilic laboratory-scale upflow anaerobic sludge bed (UASB) bioreactor design was evaluated for the treatment of winery waste water. In the first experimental study, the hydraulic retention time (HRT) was shortened from 24 h to 13 h which led to an increase in the organic loading rate (OLR) from 6,34 to 10,12 kgCOD.m-3.d-l. The recovery rate of the bioreactor, in terms of pH stabilisation was much slower for HRT’s less then 14 h, suggesting that the optimum operational HRT had been reached. At this HRT the average COD removals were between 93 and 97% and the removal rate was 10,94 kgCOD.m-3.d-1. The second experimental study was the reduction in substrate pH from 7 ,5 to 5,0. This study was performed to investigate the lowest substrate pH that the active microbial population in the bioreactor could handle so as to reduce neutralisation costs and acclimatise the microbes to lower pH’s. The lowest operational pH reached was 5,1 with a COD removal of over 90%. This has a considerable impact on the economic aspects of the winery waste water treatment process as neutralisation of the waste water will not be necessary before introducing it to the UASB bioreactor.